Characterization of Phytoene synthase 2 (Psy2) genes in wheat - Colasuonno P.; Schiavulli A.; Sonnante G.; Incerti O.; Giove S.; Giancaspro A.; Zacheo S.A.; Gadaleta A. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Phytoene synthase (Psy) is a key enzyme responsible in plant metabolism of carotenoids. Psy genes are important for their contribution to flour color and nutritional aspects in human diet since they are precursor of vitamin A. In the grass family, PSY are nuclear enzymes encoded by a small gene family consisting of three genes: Psy1, Psy2, and Psy3 localized on group 7 and 5 chromosomes. The goal of our study was to characterize Psy2 gene sequences and to verify its assessment with quantitative trait loci (QTL) involved in carotenoid expression in durum wheat. In the work we described the isolation of the Psy2 sequences on A and B genomes in durum wheat cvs. Latino and Primadur characterized by a different carotenoid content. Psy-A2 (2,593 bp) and Psy-B2 (2,646 bp) were comprised of 6 exons separated by 5 introns. Alignment with Brachypodium and rice genomes confirmed the intron/exon structure. The study localized Psy2 genes on chromosomes 5B and revealed the absence of linkage with QTLs for carotenoid content.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)